Hakikat Pemimpin dalam Ayat-Ayat Manajemen Pendidikan Islam - Nur Hayati (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to examine the verses of the Qur'an that correlate with the functions of Islamic education management and their implementation in Islamic educational institutions. The research employs a qualitative approach with library research method, utilizing primary data sources from the Qur'an, hadith, and exegesis books, as well as secondary sources from various literature on Islamic education management. The findings reveal that management principles such as planning, organizing, actuating, leadership, controlling, and evaluation have been explained in the Qur'an. Leadership in Islamic education is a trust (amanah) aimed at directing, guiding, and managing educational institutions based on the values of the Qur'an and Sunnah. The ideal leader in Islam must possess the qualities of shidiq (truthfulness), amanah (trustworthiness), tabligh (communicative), and fathanah (intelligence), and should emulate the leadership of the prophets. Leadership functions encompass planning, organizing, actuating, and controlling, carried out through the principles of deliberation (shūrā), justice (al-'adl), and responsibility (mas'uliyyah). The leader's role is highly strategic as a role model, planner, supervisor, and problem solver. The implementation of leadership values in QS. Al-Baqarah/2:30 and QS. An-Nisa/4:59 serves as a foundation for the effective and professional governance of Islamic educational institutions oriented toward developing students' character of faith and noble morals